Missiological implications of Paul"s mission strategies and lessons for urban missionaries - Alawode, Akinyemi O. (HTS teologiese studies, 2025)
The terms ‘mission,’ ‘missions’ and ‘missionary’ within the Christian context are often associated with the goal of Christianising remote or rural areas. Many reports from mission fields are characterised by events and issues that highlight the needs of rural churches or missions. Some missionaries, particularly in Africa, argue that missionary work is misplaced in urban settings. It is intriguing, therefore, that one of the foremost missionaries of biblical times, the Apostle Paul, exemplifies urban missions. This article examined the personality of the Apostle Paul, his mission expeditions, the strategies and impacts of his journeys and the lessons for urban church planters. The author employed a descriptive research method and concluded, ‘The life and ministry of Paul, as documented in the Bible, could be called a manual for urban mission agencies and missionaries. His call, character and commitment are his most potent strategies for fulfilling the Great Commission’.Contribution: The article contributes to the field of missiology by suggesting that missionaries and mission practitioners should emulate Paul’s life and ministry to achieve successful urban mission work.